PROBLEMATICS AND PROPOSED RESEARCH MODEL TO SUPPORT AGRIBUSINESS PERFORMANCE: A CASE STUDY IN PACITAN - Steffanie Setiawan; Helena Sidharta (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
Agribusiness is crucial to the development of agriculture, particularly in regions where farming is the primary source of income for the majority of the populace. In agribusiness, challenges are frequently brought on by a lack of infrastructure, infrastructure assistance, and government support. The agribusiness growing in Pacitan is the main topic of this study. In order to support the performance of agribusiness, this research aims to identify the issues that exist in Pacitan. The information was gathered through literature reviews and examining the farmers' project model construction. The interviews indicate that Pacitan has problems with the infrastructure, which has to be addressed, and the lack of human resources among the farmers in terms of the skills and knowledge required to boost the level of their output. The findings indicate that irrigation is still a significant infrastructure necessity for Pacitan's agricultural sector. This has an impact on Pacitan's agricultural output outcomes, which has an impact on the industry's poor performance in reaching excellence. The researcher suggests a model using a relationship approach between skills, knowledge, infrastructure, and government support to help achieve success in enhancing agriculture performance in Pacitan.